Overview of Interleukin-6 Levels in COVID-19 (Coronavirus Disease 2019) Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Adhika Rahman; Irvan Medison; Afriani Afriani (HM Publisher, 2023)
Background: COVID-19 infection can cause an exaggerated immune response. This immune response is associated with an increase in proinflammatory cytokines, especially interleukin-6 (IL-6). High IL-6 levels are found in the acute stage of COVID-19, and IL-6 can induce an excessive humoral inflammatory response. This study aimed to provide an overview of IL-6 levels in coronavirus disease 2019 (COVID-19) patients at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: Descriptive observational study of 102 research subjects. Observations on sociodemographic, clinical, and laboratory data were carried out in this study. Univariate analysis was carried out using SPSS version 25. Results: Patients with symptom onset <7 days had higher IL-6 levels than those with an onset of more than 7 days. Patients with critical degrees have the highest IL-6 levels compared to moderate and severe degrees. Patients with more than 1 comorbid had higher IL-6 levels than patients who had no comorbid or only had 1 comorbid. Patients with <21 days of treatment had higher IL-6 levels than patients with more than 21 days of treatment. Conclusion: COVID-19 patients at Dr. M. Djamil General Hospital, Padang, Indonesia, with an onset of less than 7 days, a critical degree, and more than 1 comorbidity have higher IL-6 levels.